1994
DOI: 10.1002/bem.2250150606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2.45‐GHz microwave radiation and phorbol ester 12‐O‐tetradecanoylphorbol‐13‐acetate on dimethylhydrazine‐induced colon cancer in mice

Abstract: The purpose of this study was to investigate the effects of 2.45 GHz microwave (MW) radiation on dimethylhydrazine (DMH)-induced colon cancer in mice. The subjects were 115 Balb/c mice 4 weeks of age. The animals were divided into group A (control), group B (DMH), group C (DMH+MW), and group D [DMH + 12-O-tetradecanoylphorbol-13- acetate (TPA)]. Radiation (10 mW/cm2) was delivered dorsally with the E field parallel to the mouse's long body axis in an anechoic chamber. Radiations were administered 3 hr daily, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 15 publications
(5 reference statements)
0
14
0
2
Order By: Relevance
“…45,52,53 Long-term studies in rats and mice have shown no biologically meaningful effects. [54][55][56][57][58] A 2-fold increase of lymphoma in a transgenic mouse model predisposed to develop this malignancy 24 was not replicated in a larger, more rigorous investigation 59 specifically designed to address limitations of the Repacholi et al study, 24 and other long-term studies have also not shown an excess of lymphomas. 55,57,58 While the numbers of NHL cases was substantial in this investigation of the role of cellular phones and NHL, there were several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…45,52,53 Long-term studies in rats and mice have shown no biologically meaningful effects. [54][55][56][57][58] A 2-fold increase of lymphoma in a transgenic mouse model predisposed to develop this malignancy 24 was not replicated in a larger, more rigorous investigation 59 specifically designed to address limitations of the Repacholi et al study, 24 and other long-term studies have also not shown an excess of lymphomas. 55,57,58 While the numbers of NHL cases was substantial in this investigation of the role of cellular phones and NHL, there were several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are important, but their relationship to carcinogenesis in vivo is unclear. (43) report no effect of RF exposure (2.45 GHz exposed 3 hr/day, 6 days/week for 5 months; average SAR 10-12 W/kg) on chemically induced colon cancer in mice. Rotkovska et al (44) found that exposure of mice to low-level RF fields from a police radar (34 GHz) did not affect biological parameters that could initiate any pathologic process.…”
Section: Promotion and Progression Studiesmentioning
confidence: 97%
“…Fa re ler, araş tır ma sü re sin ce [19][20][21] o C sa bit sı caklık ta ve 12 sa at ay dın lık/ka ran lık dö nem le rin bulun du ğu özel ha zır lan mış, oto ma tik ola rak kli ma ti ze edi len oda lar da ko run du ve nor mal pellet cin si yem ile bes len di. De ney sü re sin ce hayvan lar gün lük ola rak kon trol edil di ve haf ta lık ki lo ta ki bi ya pıl dı.…”
Section: Hay Van Larunclassified
“…Çok lu doz uy gu la ma la rın da, 5-6 haf ta lık ve 24-30 gr ara sı ağır lı ğın da ki fa re le re, 5-20 haf ta ara lı ğın da haf ta da bir kez de ği şik doz lar da (6.8-20 mg/kg) DMH ve ril miş ve son DMH en jek si yo nundan son ra de ği şik sü re ler de (10 haf ta-2 yıl) bek leti len de ney hay van la rın da fark lı oran lar da (%26-100) ko lon tü mör le ri nin ge liş ti ği, bun la rın ço ğun luk la (%86-98) dis tal ko lo na yer leş ti ği tes pit edil miş tir. 6,19,[21][22][23][24][25] Baş ka bir ça lış ma da ise di şi ve erkek fa re ler ara sın da kan ser oluş ma sı açı sın dan farklı lık lar göz len me di ği ifa de edil miş tir. 26 Thu lu sen ve ar k. yap tık la rı ça lış ma da, ko lon kan se ri ni in dük le mek için 20 mg/kg DMH'yi, 12 haf ta bo yun ca, sekiz haf ta lık di şi Balb/C tü rü fa rele re haf ta da bir kez s.c yol dan en jek te et miş ler ve son DMH do zun dan 12 haf ta son ra fa re ler de %100 ko lon kan se ri ge liş ti ği ni bil dir miş ler dir.…”
Section: Tar Tiş Maunclassified